2015
DOI: 10.1097/gox.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Venous Graft for Full-thickness Palpebral Reconstruction

Abstract: Summary:Full-thickness palpebral reconstruction is a challenge for most surgeons. The complex structures composing the eyelid must be reconstructed with care both for functional and cosmetic reasons. It is possible to find in literature different methods to reconstruct either the anterior or posterior lamella, based on graft or flaps. Most patients involved in this kind of surgery are elderly. It is important to use easy and fast procedures to minimize the length of the operation and its complications. In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… 13 Some defects can be closed only with skin sutures, but deeper defects and those under tension require layered closure. 10 , 11 , 16 , 19 , 20 The use of a 1-step procedure such as the free tarsoconjunctival graft and flap would inevitably cause eyelid retraction. 21 , 22 The Mustarde flap as well as the modified rotational advancement cheek flap can wrap a large defect consisting of as much as 75% of eyelid by providing a more physiological structure and little disturbance of the donor site.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Some defects can be closed only with skin sutures, but deeper defects and those under tension require layered closure. 10 , 11 , 16 , 19 , 20 The use of a 1-step procedure such as the free tarsoconjunctival graft and flap would inevitably cause eyelid retraction. 21 , 22 The Mustarde flap as well as the modified rotational advancement cheek flap can wrap a large defect consisting of as much as 75% of eyelid by providing a more physiological structure and little disturbance of the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the properties of elasticity, smoothness, and concavity, the venous graft conforms to the globe without inducing a chronic inflammatory reaction on the bulbar conjunctiva or on the cornea[ 41 ]. Scevola et al [ 42 ] showed that VG is a good technique for palpebral reconstruction because it is safe, fast, and easily reproducible when compared with a chondroseptal graft.…”
Section: Graft Transplantationmentioning
confidence: 99%